European Union policy for sustainable development – foundation, perspectives and results during the COVID-19 pandemic - MacGregor Pelikánová, Radka (<center>Conference Proceedings Determinants Of Regional Development</center>; No 2 (2021): Conference Proceedings - VIII International Scientific Conference Determinants of Regional DevelopmentDO - 10.14595/CP/02/002, 2021)
The modern concept of sustainability as incorporated in the UN Agenda 2030 appears to be at the very heart of the EU endeavors under the auspices of the policy for sustainable development. However, the famous ten-year strategy Europe 2020 for a smart, sustainable and inclusive growth just ended and the launched drive for sustainable development seems to be overshadowed by the COVID-19 pandemic. Arguably, the COVID-19 pandemic can be seen as any other crises and thus implying threats as well as an opportunity to get down to true roots and values, and could ultimately lead to a more eager, just and fair sustainable development. Hence, it is instrumental to review the modern EU framework and setting, and to identify and assess key parameters of the EU policy for sustainable development. Consequently, appropriate EU strategies and their 24 initiatives are identified along with all 17 Sustainable Development Goals of the UN Agenda 2013 and, based on that, a holistic and heuristic Meta-Analysis is performed to assess (I) their foundations, including their ethical dimension, (II) current perspectives and (III) results based on indices. This is organically done in the recent contextual teleologism while using simplified Delphi scoring and Eurostat indices and while reflecting the impact of the COVID-19 pandemic. The result offers a set of valuable inputs leading to propositions that there is a lack of  a common foundation, discrepancy in ethical dimension, manipulation in perspectives and, most importantly, a strong fragmentation and artificial tying of desired results, such as the Green Deal and COVID-19. The EU policy for sustainable development is at the crossroads and COVID-19 is an opportunity to become more consistent, legitimate, effective and efficient.